Manuscript Selection in a Literature Review: “Free-Full-Text-or-Next” as a New Criterion - Galli, Fabio (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
Literature inclusion and exclusion (E/I) criteria are a fundamental selection methodology in different applications. Mainly, the E/I criteria are identified and chosen with respect to the question for which the manuscript itself is produced, thus allowing the selection of the literature. This procedure is not always related to the economic availability of independent subjects (e.g., researchers, authors, students) or even institutions in low-income areas or with little willingness to cover the use of paid materials. The proposed criterion (free-full-text-or-next) aims to support independent subjects (without affiliations) or subjects belonging to economically disadvantaged areas.